Phonological Errors in President Prabowo's State of the Nation Speech: Implications for the Development of the Official Variety of Indonesian Language - Wasilatul Bariroh; Dra. Yanti Linarsih (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2026)
This study aims to describe the forms of phonological errors in President Prabowo Subianto's state speech which was broadcast on the tvOneNews YouTube channel on October 20, 2024. Using a qualitative descriptive methodology, we analyzed speech recordings for 47 minutes and 23 seconds ( 8,500 words). The analysis identified three categories of phonological variations: phoneme addition (5 instances), phoneme removal (8 instances), and phoneme change (17 instances). The most dominant forms are phoneme changes, specifically vowel reduction (/a/ → /&partial;/) and diphthongs simplification (/ai/ → /e/, /au/ → /o/). Statistical analysis using spectral analysis software (Praat v6.1.27) revealed that speech speed (3.2 syllables/second) was the main causal factor for phonological variation, rather than local dialects or nonformal language habits as previously hypothesized in a similar study. These findings are in line with universal psycholinguistic principles regarding vowel reduction in fast speech. The study found that 47% of the variation was a systematic pattern (frequency ≥5 occurrences), indicating stable idiolects rather than random errors. These findings have implications for public speaking training programs at institutions such as LAN (State Administration Institute) and Language Centers, suggesting that formal language development requires attention to phonological aspects, in particular pronunciation accuracy and speech speed management, rather than mere prescriptive normative.